The Role of Robotic Mechanotherapy in the Recovery of Mobility in Patients after an Acute Cerebrovascular Accident - Aziza A. Biykuzieva1, Durdona M. Ahmedova2, Adibakhon A. Usmankhodjaeva3, Olga N. Visogortseva4, Eka (Institute of Medico-legal Publications Pvt Ltd, 2020)
Hemiparesis of various severity is a common type of motor disorder resulting from an experience of astroke. It is motor disorders that lead to the disruption of such categories of activity as the ability to move andself-care, which entails a limited patient mobility. The study has included 35 patients with motor disordersresulting from acute cerebrovascular accidents (CA), and the patients have undergone medical rehabilitation.Clinical research method (Ashworth and Rivermead scales) and mathematical statistics have helped assessthe positive effects of robotic mechanotherapy, which was used in the rehabilitation of stroke patients.As a result of rehabilitation measures with the use of robotic mechanotherapy, 68.2% of the examined subjectshave developed significant strength in the hand, and 45.5% - in the leg (p?0.005). In the remaining subjects,no significant improvement in the motor function has been observed, although mobility has improved in allexamined patients and the average Rivermead mobility index has been 11.4±2.1 out of 15 (p <0.001).